Didactic strategy to strengthen communication skills in police students, with extension to students from the rural sector of Sibaté in Cundinamarca (Colombia) - Montoya Párraga, Lucy Alcira; García Sarria, Juan José; González Cortés, Armando (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The didactics is carried out with police students from the Gonzalo Jiménez de Quesada School of Noncommissioned Officers and Executive Level, which will multiply the rural students of the Sibaté municipality. The purpose of the project was to design a pedagogical didactic strategy that allows to strengthen the Communicative Skills by implementing literacy, in the police students and at the same time the students of the Rural Educational Institutions of Sibaté Cundinamarca. Methodologically, the project was carried out using the qualitative approach of an ethnographic nature. In conclusion, the implementation of several reading and writing activities was motivated, with extension to students from the Rural sector.